SOCIOLINGUISTIC ANALYSIS OF VERBAL AFFIXATION OF AKLAN: A PEDAGOGICAL CLASSROOM WORK AS BASIS TO GRAMMATICAL RULE FORMULATION - Gonzales, Elson (International Journal of Arts, Sciences and Education, 2023)
The study aimed to analyse the affixes of the Aklanon language according to its clusters: Aklanon-Inakeanon, Aklanon-Buruanganon, Aklanon-Malaynon, and Aklanon-Nabasnon in the lens of the sociolinguistic approach in order to create materials that can be used in the teaching of Mother Tongue-Based Multilingual Education (MTB-MLE) in the province of Aklan. Specifically, it aspired to develop a grammatical rule towards the development of regional languages ​​especially in the aspect of verbs. The design was descriptive-analytical using purposive sampling; descriptively analysed the data according to each corpus in five (5) domains: Livelihood, Celebration, Superstition/Belief, Literature, and Daily Life. It was found that almost all the suffixes applied to each corpus were the same, but differed only in pronunciation due to the voiced velar fricative “ɣ”. There was also a morphophonemic change in each corpus collected. The study suggested that there should be an emphasis on the formulation of pedagogical materials according to the need and its authors should be native.